Eksplorasi Endapan Bauksit Menggunakan Metode Polarisasi Terimbas dan Resistivitas di Desa Sebemban, Kalimantan Barat - Handika; Arman, Yudha; Muhardi, Muhardi (Jurusan Fisika, Universitas Bangka Belitung, 2025)
Tayan Hilir District, West Kalimantan Province, Indonesia, is characterized by the presence of economically valuable mineral resources, particularly bauxite deposits. This study aims to delineate the distribution of bauxite deposits in Sebemban Village, Tayan Hilir District, using integrated geophysical approaches. The investigation employed the induced polarization (IP) and electrical resistivity methods with a dipole–dipole electrode configuration. Resistivity and chargeability measurements were conducted along three survey lines, each 156 m in length with an electrode spacing of 4 m. The results show that the resistivity values range from 45.36 to 367.177 Ω·m, while the chargeability values vary between 16.9 and 878.80 ms. The subsurface stratigraphy of the study area comprises latosol, bauxite, saprolite, and bedrock units, including granodiorite and quartz diorite. Bauxite mineralization was identified at shallow depths, commencing at approximately 0.6 m below the ground surface. These results indicate that the combined application of resistivity and induced polarization methods is effective for identifying and characterizing near-surface bauxite deposits in the study area.